All Cubic‐Phase δ‐TAGS Thermoelectrics Over the Entire Mid‐Temperature Range. Issue 17 (26th January 2023) - Ma, Baopeng; Ren, Hongrui; Zhang, Fudong; Peng, Zhanhui; He, Hailong; Cui, Minchao; Ge, Zhenhua; Li, Bingyu; Wu, Wenwen; Liang, Pengfei; Xiao, Yu; Chao, Xiaolian; et al.
Abstract: GeTe‐based pseudo‐binary (GeTe) x (AgSbTe2 )100− x (TAGS– x ) is recognized as a promising p ‐type mid‐temperature thermoelectric material with outstanding thermoelectric performance; nevertheless, its intrinsic structural transition and metastable microstructure (due to Ag/Sb/Ge localization) restrict the long‐time application of TAGS‐ x in practical thermoelectric devices. In this work, a series of non‐stoichiometric (GeTe) x (Ag1‐ δ Sb1+ δ Te2+ δ )100− x ( x  = 85∼50; δ = ≈0.20–0.23), referred to as δ‐TAGS‐ x, with all cubic phase over the entire testing temperature range (300‐773 K), is synthesized. Through optimization of crystal symmetry and microstructure, a state‐of‐the‐art ZTmax of 1.86 at 673 K and average ZTavg of 1.43 at ≈323–773 K are realized in δ‐TAGS‐75 (δ = 0.21), which is the highest value among all reported cubic‐phase GeTe‐based thermoelectric systems so far. As compared with stoichiometric TAGS‐ x, the remarkable thermoelectric achieved in cubic δ‐TAGS‐ x can be attributed to the alleviation of highly (electrical and thermal) resistive grain boundary Ag8 GeTe6 phase. Moreover, δ‐TAGS‐ x exhibits much better mechanical properties than stoichiometric TAGS‐ x, together with the outstanding thermoelectric performance, leading to a robust single‐leg thermoelectric module with ηmax of ≈10.2% and P max of ≈0.191 W. The finding in this work indicates the great application potential of non‐stoichiometric δ‐TAGS‐ x in the field of mid‐temperature waste heat harvesting. Abstract : Crystal structure engineering and grain boundary phase engineering endow δ‐TAGS‐ x with excellent thermoelectric properties and potential application in the practical thermoelectric devices. As compared with stoichiometric TAGS‐ x, the remarkable thermoelectric performance achieved in cubic δ‐TAGS‐ x can be attributed to the alleviation of highly (electrical and thermal) resistive grain boundary Ag8 GeTe6 phase.